2020
DOI: 10.15252/embr.201949752
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of glycolysis promotes cardiomyocyte proliferation after injury in adult zebrafish

Abstract: Cardiac metabolism plays a crucial role in producing sufficient energy to sustain cardiac function. However, the role of metabolism in different aspects of cardiomyocyte regeneration remains unclear. Working with the adult zebrafish heart regeneration model, we first find an increase in the levels of mRNAs encoding enzymes regulating glucose and pyruvate metabolism, including pyruvate kinase M1/2 (Pkm) and pyruvate dehydrogenase kinases (Pdks), especially in tissues bordering the damaged area. We further find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 78 publications
4
72
0
Order By: Relevance
“… 24 , 92 Recent studies have revealed that pyruvate dehydrogenase kinase (PDK) regulates glycolysis and pyruvate metabolism of cardiomyocytes of the border area in zebrafish after injury. 93 Moreover, the loss of PDK4 can increase the proliferation of cardiomyocytes and improve left ventricular function after MI and reduce remodeling. 94 These findings suggest that energy metabolism plays a critical role in cardiomyocyte proliferation after injury.…”
Section: Proliferation and Mitosis Of Pre-existing Cardiomyocytesmentioning
confidence: 99%
“… 24 , 92 Recent studies have revealed that pyruvate dehydrogenase kinase (PDK) regulates glycolysis and pyruvate metabolism of cardiomyocytes of the border area in zebrafish after injury. 93 Moreover, the loss of PDK4 can increase the proliferation of cardiomyocytes and improve left ventricular function after MI and reduce remodeling. 94 These findings suggest that energy metabolism plays a critical role in cardiomyocyte proliferation after injury.…”
Section: Proliferation and Mitosis Of Pre-existing Cardiomyocytesmentioning
confidence: 99%
“…Fetal cardiomyocyte energy production occurs primarily by glycolysis in rodents, although there is evidence of mid-to-late gestational onset of oxidative metabolic pathways in some large mammals, such as sheep [ 28 ]. In zebrafish hearts, increased glycolysis and pyruvate metabolism is noted in cardiomyocyte proliferation and regenerative repair of the heart [ 29 ]. In rodent hearts, cardiomyocyte metabolism undergoes rapid transition from glycolytic to fatty acid oxidation in the first few days after birth with postnatal increase in oxygen consumption [ 30 ].…”
Section: Overview Of Postnatal Cardiomyocyte Maturationmentioning
confidence: 99%
“…Human and pig mitochondrial dynamics during heart development are not well-characterized, but, given the shared atmospheric oxygen environment between these species and rodents, along with the incidence of human neonatal mitochondrial cardiomyopathies associated with oxidative phosphorylation defects [ 36 , 37 , 38 ], it is likely that a similar mitochondrial maturation occurs in large mammal cardiomyocytes. In the regenerative adult zebrafish model, the state of the mitochondria more closely resembles that of the neonatal mouse, with increased glycolysis and pyruvate metabolism noted in proliferative cardiomyocytes and regenerative repair of the heart [ 29 ]. These data support a link between the extent of mitochondrial maturation and cardiomyocyte proliferative capacity in the heart.…”
Section: Overview Of Postnatal Cardiomyocyte Maturationmentioning
confidence: 99%
“…Indeed, a recent study has shown that the transcriptome of zebrafish border zone CMs is more similar to embryonic CMs then to remote myocardial CMs originating from the same hearts [88]. This reversion back to an embryonic state is likely key to unlock their proliferative potential as inhibiting their dedifferentiation, including the induction of glycolysis, prevents CMs from proliferating effectively [86][87][88][89].…”
Section: Cardiomyocytesmentioning
confidence: 99%